The phenomenon of court-servant's control in Abbasid power and its repercussion on caliphate status during the reign of caliph al-Muqtadir Bi-Allah (907 - 932 AD/ 295–320 AH) - Ali Khudair Al- Hadrawi (Zien Journals, 2022)
This research aims to study the phenomenon of court-servants' control in Abbasid power during the reign of the caliph (successor) Abu’l-Faḍl Jaʿfar ibn Ahmad al-Muʿtaḍid (282 -320 AH / 895 –932 AD), better known by his regnal name Al-Muqtadir bi-Allah. Furthermore, this study represents as an academic attempt aimed mainly at studying the political situation and reviewing one of the manifestations of the political and administrative corruption, deterioration, and decline inflicting the caliphate institution. This issue had not stopped when the Turkish officials intervened and controlled the Abbasid state , in every possible way , but it reached to different types of intervention represented by employing all human means such courtiers chamberlains and eunuchs , court -servants and gate-keepers. More importantly, Al-Muqtadir bi-Allah became a tool or puppet in their hands directing him as they please
Keywords: puppet; importantly; types; represented